2008
DOI: 10.1111/j.1582-4934.2008.00399.x
|View full text |Cite
|
Sign up to set email alerts
|

microRNA expression in lymphoid malignancies: new hope for diagnosis and therapy?

Abstract: AbstractmicroRNAs are a newly discovered class of short (∼22 nt) naturally occurring single-stranded RNA molecules that regulate the expression of target genes post-transcriptionally. Despite only being discovered 7 years ago, microRNAs have been implicated as key regulatory molecules in nearly every biological process examined so far and abnormal expression of microRNAs have been linked to many forms of disease including cancer where they can function as both tumour-suppressors and oncogenes. So why are micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(30 citation statements)
references
References 130 publications
0
30
0
Order By: Relevance
“…Several diagnostic tools have been implemented for the detection and quantification of microRNA expression levels, such as northern blotting, semiquantitative in situ hybridization, quantitative real-time PCR, fluorescencelabelled bead technology, and array hybridization with various probe sets and alternative protocols and methods for microRNA profiling of FFPE specimens, which are based on real-time PCR or microarray-hybridization (Lawrie, 2008;Streichert et al, 2011;Khan et al, 2011;Streichert et al, 2012;Josephine Wu et al, 2013). For example, the basic MiRNA profiling that identified that the induction of many miRNAs was coincident with the different stages of differentiation was proved by Volinia and colleagues (Volinia et al, 2006) using hierarchical clustering analysis of 540 samples including 363 from six of the most frequent solid tumour types (breast, colon, lung, pancreas, stomach, and prostate).…”
Section: Micrornas As Potential Biomarkers For Cancer Diagnosis and Pmentioning
confidence: 99%
“…Several diagnostic tools have been implemented for the detection and quantification of microRNA expression levels, such as northern blotting, semiquantitative in situ hybridization, quantitative real-time PCR, fluorescencelabelled bead technology, and array hybridization with various probe sets and alternative protocols and methods for microRNA profiling of FFPE specimens, which are based on real-time PCR or microarray-hybridization (Lawrie, 2008;Streichert et al, 2011;Khan et al, 2011;Streichert et al, 2012;Josephine Wu et al, 2013). For example, the basic MiRNA profiling that identified that the induction of many miRNAs was coincident with the different stages of differentiation was proved by Volinia and colleagues (Volinia et al, 2006) using hierarchical clustering analysis of 540 samples including 363 from six of the most frequent solid tumour types (breast, colon, lung, pancreas, stomach, and prostate).…”
Section: Micrornas As Potential Biomarkers For Cancer Diagnosis and Pmentioning
confidence: 99%
“…miRNAs are proposed to play a direct role in oncogenesis, as they can function as both oncogenes and tumor-suppressor molecules. Currently, at least three mechanisms are understood whereby miRNAs are deregulated in cancer: i) chromosomal lesions at regions encoding microRNAs, ii) defects in the miRNA biosynthetic pathway machinery, and iii) epigenetic regulation (4). miRNAs also have been demonstrated to have diagnostic, prognostic and therapeutic potential in cancer (5)(6)(7).…”
Section: Introductionmentioning
confidence: 99%
“…The potential importance of microRNAs in cancer is implied by the finding that the majority of human microRNAs are located at cancer-associated genomic regions (Calin et al, 2004). There is now overwhelming evidence that dysfunctional expression of microRNAs is a common, if not ubiquitous, hallmark of cancer in general, including lymphomas (Lawrie, 2008;Iorio & Croce, 2009). Much has been done to catalogue those miRNAs that are aberrantly-expressed in many types of lymphomas, and this information shows great promise in refining and adding to current classification systems (Westin & Fayad, 2009).…”
Section: Discussionmentioning
confidence: 99%